Risk of carotid plaques according to triglyceride-glucose index stratified by thyroid function: A cross-sectional study. - Hye Jeong Kim; Seong Soon Kwon; Sang Joon Park; Dong Won Byun; Kyoil Suh; Myung Hi Yoo; Duk Won Bang; Hyeong Kyu Park (PLoS ONE, 2022)
Background Recent studies have indicated that the triglyceride-glucose (TyG) index or subclinical thyroid dysfunction is associated with carotid plaques, a predictor of cardiovascular disease risk. However, evidence for this association is limited and inconsistent. This study aimed to evaluate the risk of carotid plaques according to TyG index and thyroid function status in the general population. Methods A total of 2,931 individuals who underwent carotid ultrasound as part of a comprehensive health examination at the Health Promotion Center of Soonchunhyang University Hospital were retrospectively reviewed. Based on the TyG index and thyroid function status, the participants were divided into six groups: LoTyG-SHyper (low TyG index with subclinical hyperthyroidism), LoTyG-Eu (low TyG index with euthyroidism), LoTyG-SHypo (low TyG index with subclinical hypothyroidism), HiTyG-SHyper (high TyG index with subclinical hyperthyroidism), HiTyG-Eu (high TyG index with euthyroidism), and HiTyG-SHypo (high TyG index with subclinical hypothyroidism). A multivariate logistic regression analysis was conducted to determine the risk of carotid plaques. Results The proportion of participants with significant carotid plaques was significantly different among the six groups (p<0.001, p for trend<0.001). The odds ratio (OR) and 95% confidence interval (CI) for significant carotid plaques were significantly higher in the HiTyG-SHypo group than in the LoTyG-Eu group, even after adjusting for confounding variables including sex, age, smoking, obesity, hypertension and diabetes mellitus (OR 1.506, 95% CI 1.045-2.170, p = 0.028). The OR of significant carotid plaques was higher in the HiTyG-Eu group than in the LoTyG-Eu group; however no associations were observed after additional adjustment for confounding variables. Conclusion The TyG index and thyroid function status are important predictors of the risk of carotid plaques in healthy individuals. Early evaluation of carotid plaques may be necessary for subjects with high insulin resistance and subclinical hypothyroidism.